Microsoft .NET, distributed applications : integrating XML web services and .NET remoting - MacDonald, Matthew (Microsoft Press, 2003)
Make the jump to distributed application programming using the .NET Framework-and introduce a new level of performance, scalability, and security to your network and enterprise applications. Expert .NET developer Matthew MacDonald shares proven techniques for fully exploiting .NET Remoting, XML Web services, and other .NET technologies and integrating them into your real-world solutions. MacDonald digs into key .NET building blocks and architectural issues, explaining which features and designs will best serve your customized distributed application projects-and when to use them. Case studies with full code examples illustrate these practical techniques in action, as well as demonstrating their benefits and tradeoffs.